Public-Private Partnerships: A Solution for Infrastructure Development in the UK? Case Study of the London Underground Public-private Partnership Project - Khoteeva, Margarita; Khoteeva, Daria (International Review of Management and Marketing, 2017)
The article examines the role of public-private partnerships in infrastructure development in the UK through the analysis of the London Underground PPP project implemented in 1997-2008. The study is based on the theory analysis of the development of the concept of public-private partnerships in the UK in the recent decades and the factual and statistical information regarding the events that led to the failure of the London Underground PPP project. The study is motivated by the question why the London Underground PPP project resulted as unsuccessful and if the reasons of failure can be attributed to other PPP infrastructure projects. The findings of the study illustrate the reasons for the failure of the London Underground PPP project and the lessons learned from it. The failure of the PPP project came from the combination of factors, such as poor conditions of infrastructure, lack of financial and risk management systems, poor corporate governance of the private sector company, public sector's inability to manage the contract, and a tied supply chain. The findings have shown that the question of whether such failure can occur in other infrastructure development PPP project still remains open and needs to be closely assessed in each case. Keywords: Public-private partnerships, Infrastructure, Transport JEL Classifications: R4, H7, H1